Sanksi Pidana Terhadap Penumpang Yang Melanggar Tata Tertib Di Dalam Pesawat Udara Berdasarkan Undang-Undang Nomor 1 Tahun 2009 Tentang Penerbangan - Dewa Ayu Made Mayani; M. Lucky Septian Mulia; Muhamad Dwi Septiawan; Muhamad Alyo Vidawarman; Sunarto (Consensus : Jurnal Ilmu Hukum, 2022)
Article 54 of the Law No. 1 of 2009 on Aviation regulates the types of violations of order occurring on aircraft. Article 1 regulates aviation as a system consisting of the exploitation of airspace, aircraft, airport, air transportation, aviation navigation, safety and security, living environment, as well as support facilities and other public facilities. The type of breaches of order that occurred in aircraft during flight is the subject of this study.